ANALISIS DOSIS RADIASI TERHADAP PARAMETER HEMATOLOGI BERDASARKAN FAKTOR DEMOGRAFI PEKERJA RADIASI DI RSUP DR. M. DJAMIL PADANG - Rihadatul Aisy Syofyani Nasution; Dian Milvita; Rico Adrial (Jurnal Fisika Unand, 2025)
Research on the analysis of radiation dose on hematological parameters based on demographic factors of radiation workers has been conducted at Dr. M. Djamil Hospital Padang. The study aims to analyze the impact of radiation dose on hematological parameters of radiation workers and to evaluate the role of demographic factors such as age, years of service, profession, and work unit in determining the hematological condition of workers. The study utilized secondary data on radiation dose levels of radiation workers from 2022-2023, measured using Thermoluminescence Dosimeter (TLD) badges, and secondary hematological data from the same period obtained from the results of Medical Check-Ups (MCU) of radiation workers. The relationship between radiation dose, hematological parameters (red blood cells, white blood cells, and platelets), and demographic factors was evaluated using ANOVA and Kruskal-Wallis statistical analysis tests. The results of the study showed that the radiation dose received did not significantly affect hematological parameters. However, age and work experience significantly influenced red blood cell counts. Occupation and work unit did not show a significant relationship with hematological parameters.